Thomas the tank engine easy-to-read treasury - Awdry, Christopher (Melbourne, Reed Books, 1997)
This storybook based on the adventures of Thomas the Tank Engine is designed for beginner readers. It contains three stories in one.
3-5
Keywords: Language